Information Technology Governance Using the COBIT 2019 Framework at PT. Bitung Branch Fisheries - Mambu, Joe Yuan; Lumingkewas, Cherry (SEULANGA SYSTEM PUBLISHER, 2024)
Information Technology (IT) governance is crucial for the success of companies in the current digital era. PT. Bitung Branch Fisheries, which operates in the fisheries sector in the Bitung area, faces challenges in effective IT management and governance. Adopting the COBIT 2019 framework, the company hopes to improve operational efficiency, reduce security risks, and ensure regulatory compliance. This research aims to explore the implementation of COBIT 2019 at PT. Bitung branch fisheries, identifying problems and potential improvements, as well as the impact on IT performance and governance. Focus on PT's unique context. The Bitung branch fisheries differentiate it from previous studies, hoping that the results will benefit companies and the IT governance community. Through a comprehensive literature review and research methodology, we analyze the design factors influencing IT governance and COBIT 2019 implementation. The results highlight APO04 as a priority object, indicating the company's attention to IT innovation. However, gaps were found in the current level of capability. We recommend strengthening the implementation of APO04, increasing managerial capabilities, and strategic collaboration to improve IT governance and innovation at the PT. Bitung branch of fisheries. In conclusion, this research provides valuable insights for companies and the IT governance community in implementing COBIT 2019 to improve performance and compliance in the ever-evolving digital era.